THE IMPACT OF DIGITAL LITERACY AND ENTREPRENEURIAL ORIENTATION TO SURAKARTA BATIK SMEs PERFORMANCE (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
The purpose of this research is to (1) determining the impact of digital literacy knowledge on the performance of Batik SMEs in Surakarta, (2) determining the impact of entrepreneurial orientation on the performance of Batik SMEs in Surakarta, (3) determining of the impact digital literacy knowledge and entrepreneurial orientation on the performance of Batik SMEs in Surakarta. The object of this research is Batik SMes in the Surakarta, which is the guidance of the Surakarta Cooperative and SMEs Service, and 95 of the SMEs were the samples. This study used descriptive quantitative method with data collection through questionnaires and multiple linear regression data analysis techniques. The result of this study show that (2) there was a positive and significant impact between digital literacy knowledge on the performance of Batik SMEs in Surakarta with the t count (2,321) > the t table value (1,986). (2) there was a positive and significant influence between entrepreneurial orientation on the performance of Batik SMEs in Surakarta with the t count (7,379) > the t table value (1,986). (3) there was a positive and significant influence between digital literacy knowledge and entrepreneurial orientation on the performance of Batik SMEs in Surakarta with the F count value (39,858) > F table value (3,905).